2022
DOI: 10.3389/fcvm.2022.952949
|View full text |Cite
|
Sign up to set email alerts
|

The roles and mechanisms of epigenetic regulation in pathological myocardial remodeling

Abstract: Pathological myocardial remodeling was still one of the leading causes of death worldwide with an unmet therapeutic need. A growing number of researchers have addressed the role of epigenome changes in cardiovascular diseases, paving the way for the clinical application of novel cardiovascular-related epigenetic targets in the future. In this review, we summarized the emerged advances of epigenetic regulation, including DNA methylation, Histone posttranslational modification, Adenosine disodium triphosphate (A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 196 publications
0
1
0
Order By: Relevance
“…Regarding MBPs, current research has found that methyl-CpG binding protein 2 (MeCP2), as a protein containing MBD, participates in the regulation of cardiac fibroblast proliferation and fibrosis via its ability to bind methylated DNA. In the transverse aortic constriction (TAC) mouse model, inhibiting MeCP2 activates fibroblasts and aggravates cardiac fibrosis [ 50 ], while the overexpression of MeCP2 alone shows lower levels of fibrosis and good cardiac repair [ 51 ]. Tao et al’s research on the mechanism of MeCP2 action showed that the use of MeCP2 inhibitors to treat cardiac fibroblasts can increase the expression of dual-specificity phosphatase 5 (DUSP5), and DUSP5 negatively regulates the ERK signaling pathway, thus promoting myocardial fibrosis [ 39 ].…”
Section: Epigenetic Regulations Of Cfs In Cardiac Fibrosismentioning
confidence: 99%
“…Regarding MBPs, current research has found that methyl-CpG binding protein 2 (MeCP2), as a protein containing MBD, participates in the regulation of cardiac fibroblast proliferation and fibrosis via its ability to bind methylated DNA. In the transverse aortic constriction (TAC) mouse model, inhibiting MeCP2 activates fibroblasts and aggravates cardiac fibrosis [ 50 ], while the overexpression of MeCP2 alone shows lower levels of fibrosis and good cardiac repair [ 51 ]. Tao et al’s research on the mechanism of MeCP2 action showed that the use of MeCP2 inhibitors to treat cardiac fibroblasts can increase the expression of dual-specificity phosphatase 5 (DUSP5), and DUSP5 negatively regulates the ERK signaling pathway, thus promoting myocardial fibrosis [ 39 ].…”
Section: Epigenetic Regulations Of Cfs In Cardiac Fibrosismentioning
confidence: 99%